Assessing plastic and biomass-based biochar's potential for carbon sequestration: an energy-water-environment approach - Al-Rumaihi, Aisha; Alherbawi, Mohammad; Mckay, Gordon; Mackey, Hamish; Parthasarathy, Prakash; Al-Ansari, Tareq (Frontiers in Sustainability, 2023)
Biochar from waste has emerged as a vital solution for multiple contemporary issues. While the organic content and porous structure of biochar have granted it multiple benefits. Where the use of biochar is proven to be beneficial for enhancing the soil structure and water and nutrients retention ability, therefore, saving water and boosting yields in arid regions. Moreover, biochar is capable to sequester carbon from the atmosphere and permanently store it. As such, this study evaluates the potential for carbon sequestration through biochar obtained from the pyrolysis of feedstock mixtures including camel manure, date pits, high-density polyethylene (HDPE) and low-density polyethylene (LDPE), whilst enhancing water and food security. Multiple energy and water supplying sources have been considered for different project scenarios to provide a broader understanding of biochar potentials. The lifecycle analysis (LCA) approach is utilised for the assessment of net emissions, while an economic study is conducted in Aspen Process Economic Analyser (APEA) to evaluate the feasibility of the different scenarios. Finally, single and multi-objective optimisations are carried out using MATLAB's genetic algorithm to select optimal biomass blending and utilities options to fulfil the low cost and negative emissions targets. The assessment conducted for a Qatar case study indicates that the best waste blending for maximum carbon sequestration potential was 20.4% Camel manure: 27% date pits: 26.3% LDPE: 26.4% HDPE. Furthermore, the optimum char blend for maximum carbon sequestration and minimum char cost is computed. The optimal biochar mixing percentage for highest net emission was obtained at a mixing ratio of 96.8% of date pits, 1.5% of LDPE and 1.7% oof HDPE with 0% of date pits with an optimal cost of 313.55 $/kg biochar. Solar PV was selected as the best energy source in this pyrolysis study due to its reduced carbon emissions in comparison to other sources studied such as natural gas, coal and diesel. However, natural gas is selected to fulfil the economic objective. Moreover, the optimal water source was investigated including wastewater treatment, multi-stage flash and reverse osmosis desalination, where treated wastewater is selected as the optimal supply to fulfil both, economic and environmental objectives.